Legal issues in the alienation of lands for housing development projects in Peninsular Malaysia: A case study of Kedah Darul Aman - Md Dahlan, Nuarrual Hilal (Universiti Utara Malaysia, 2014)
A housing developer requires land for housing development projects.In Malaysia, the land which is to be developed into a housing development project may be originally owned by the housing developer, the developer may obtain it through purchase from an interested seller, through a joint venture agreement with the land proprietor, or through alienation of land granted by the State Authority.The alienation of land is made based on the approval of the State Authority during the application to alienate the land to the applicant housing developers.There have been cases whereby the State Authority has approved the applications to alienate the land to the housing developers without duly taking into consideration the capability and suitability of the applicant housing developers concerned in carrying out the intended housing development project and the suitability of the land.The incapability of the developers includes lack of experience of the applicant housing developers in housing development projects or lack of funds to run housing development projects.These shortcomings, in the extreme case, may result in the problematic housing development projects.The questions that arise include: Why had the State Authority approved the applications to alienate lands to incapable housing developers and/or alienated unsuitable lands? What are the power, responsibility, and liability of the State Authority in alienating lands to applicant housing developers for housing development projects? This research aims to explain the scenarios occurring in Kedah regarding the powers and responsibilities of the State Authority and its machinery in alienating lands for housing development projects to applicant housing developers.It also identifies the problems and issues in alienation of lands for housing development projects which may lead to problematic housing development projects.The methodology used in this research is a composite of the qualitative case study and legal research. Further, this research compares between the positions of the law and practice on alienation of lands in the Republic of Singapore and New South Wales, Australia.This research rounds off with the researcher recommending certain legal approaches to overcome these problems and issues in the alienation of lands to applicant housing developers for housing development projects by the State Authority in order to avoid problematic housing development projects and other pressing issues which are detrimental to the housing developers.This research also proposes certain legislative amendments to the act governing alienation of land in order to avoid possible re-occurrences of issues and problems as identified.